Market Surveillance of Filtering Facepiece (FFP)of Respirator Protective Equipment (RPE): Malaysian Perspectives. Issue 1 (May 2020) - Osman, Baderin; Leman, A.M; Razif Noraini, N.M; Afizi Shuaib, Norshah
Abstract: Filtering Facepieces (FFPs) are commonly use as personal protective equipment (PPE). It is disposable Respiratory Protective Equipment (RPE). Basically it is used for protection against dusts, particles and aerosols. Available in 3 classes FFP1, FFP2 and FFP3. Various Respiratory Protective Equipment (RPE) offered in Malaysia's market today are not being controlled and monitored by expert bodies and authorities. This has led to various perceptions among the users, especially on the quality and safety and health features of the products offered by different companies. This situation also makes it difficult for users to decide appropriate RPE based on quality and standard compliance. The tendency of consumers to choose RPE is mainly based on the price but not the technical aspect of RPE. Hence, the RPE they purchased not necessary enhance user protection, as there is no guidance available to assist user before they purchase the most appropriate RPE. This study describes market surveillance testing of FFP2 respirator from 30 different brand in Malaysia. The objective is to determine performance requirements required by the Malaysia standard. 3 types of testing were used on this study Filter Penetration, Breathing Resistance and Carbon Dioxide Content. All testing was carried out based on Malaysia Standard; MS 2323:2010 and MS2553:2014.All 30 sample were passed the breathing resistance and carbon dioxide content except 10 brand was failed the filter penetration testing. It is noticed that the user and consumer should aware with their PPE basic requirement.